2021
DOI: 10.2147/jpr.s303998
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Administered Analgesic Treatment in Italian Emergency Medical Services: A Nationwide Survey

Abstract: Background Acute pain is common among patients requiring assistance from prehospital emergency medical services (EMS). Nonetheless, the undertreatment of pain in this context remains a frequent phenomenon. Timely and effective analgesia is a crucial feature in emergency medicine. To ensure analgesia provision, prehospital paramedics and nurses can administer analgesics via standard operating protocols or under a physician’s remote supervision. Information about such protocols in Italian EMS is lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…A recent Italian study (2021) 14 has suggested the need for EMS to improve the appropriateness of standard intervention protocols for ambulance nurses, although in our experience the presence of a specific algorithm does not seem to have been sufficient in reducing the risk of oligoanalgesia.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…A recent Italian study (2021) 14 has suggested the need for EMS to improve the appropriateness of standard intervention protocols for ambulance nurses, although in our experience the presence of a specific algorithm does not seem to have been sufficient in reducing the risk of oligoanalgesia.…”
Section: Discussionmentioning
confidence: 58%
“… 14 Oligoanalgesia, defined as a complete lack of analgesia (unrelieved pain) or an insufficient dose of analgesics (unachieved analgesia) or a postponed analgesic treatment in the prehospital emergency setting, remains a widespread phenomenon. 3 , 7 , 14 , 15 It is estimated that in prehospital emergency care pain assessment is not performed in from one-third to almost a half of all cases and even when pain is recorded, in approximately 43% of adults and 85% of paediatric patients, it is undertreated. 7 , 13 , 16 However, the management of pain in this setting is often inadequate for several reasons: reduced frequency of measuring pain, reluctance of health-care professionals to prescribe or administer opioids (defined as opiophagia), failure to use pain management guidelines, prejudices and cultural factors, fear of excessive sedation and compromising an adequate clinical assessment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations